1979
DOI: 10.1007/bf00545243
|View full text |Cite
|
Sign up to set email alerts
|

Environmental harshness, heat stress, and Marmota flaviventris

Abstract: Yellow-bellied marmots (Marmota flaviventris) were studied at three sites in central Oregon. Juveniles substantially reduced their foraging activity when equivalent black-body temperatures exceeded their upper critical temperature. Inclusion of heat stress into estimates of environmental harshness drastically reduced the differences in available foraging time between high elevation and low elevation sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The values (mean SD) used in this study (monocot: 17.95 0.34 kJ á g-dry A1 ; dicot: 17.74 0.71 kJ á g-dry A1 ) were calculated from Golley's (1961) data for April±July. These values are similar to those found by Webb (1980) for plants eaten by yellow-bellied marmots in Oregon (dicots only: 16.8±18.2 kJ á g-dry A1 ).…”
Section: Energy Requirementsupporting
confidence: 87%
See 3 more Smart Citations
“…The values (mean SD) used in this study (monocot: 17.95 0.34 kJ á g-dry A1 ; dicot: 17.74 0.71 kJ á g-dry A1 ) were calculated from Golley's (1961) data for April±July. These values are similar to those found by Webb (1980) for plants eaten by yellow-bellied marmots in Oregon (dicots only: 16.8±18.2 kJ á g-dry A1 ).…”
Section: Energy Requirementsupporting
confidence: 87%
“…But was it a true maximum? Webb (1980) showed that at sites about 1000 m in elevation, heat stress constrains foraging time in yellow-bellied marmots. My data support this ®nding.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to the difference in food abundance and thermal environment, the enclosure and field foraging environments are very different, although the enclosure conditions were within the range found at other ground squirrel colonies (Belovsky and Ritchie, 1989;Webb, 1980). Consequently, the impact of the immediate foraging environment can be determined by comparing an individual's foraging behavior in these two environments.…”
Section: Experimental Designmentioning
confidence: 99%